Karyotype Analysis of Five Iris L. (Iridaceae) Species from Turkey - Kiran, Yasar; Yavas, Tuba; Dogan, Gulden (Univ Tokyo Cytologia, 2022)
The chromosome numbers and karyotypes of five species of the genus Iris distributed in Turkey were analyzed. These taxa are I. aucheri (Baker) Sealy, I. reticulata var. reticulata M. Bieb., I. persica L., I. peshmeniana Guner & T. Hall, I. sarii Schott ex Baker. Two of them (I. sari and I. peshmeniana) are endemic in Turkey. The chromosome numbers of studied taxa were determeined as 2n= 18 (I. persica), 2n= 20 (I. sari), 2n= 24 (I. peshmeniana and I. aucheri), and 2n= 36 (I. reticulata var. reticulata). Haploid chromosome lengths varied from 53.45 mu m (I. persica) to 130.78 mu m (I. reticulata var. reticulata) among species. Karyotype analysis indicated that Iris taxa generally have median (m), submedian (sm), and subterminal (st) chromosomes. In addi-tion, only I. sari has two terminal (T) chromosome pairs. The karyotype of I. peshmeniana was determined for the first time.
Keywords: Iridaceae; Iris; Chromosome number; Karyotype; Turkey